Problemy ortograficzne ukraińskich uczniów starszych klas szkoły podstawowej na Pomorzu – na podstawie wypowiedzi zgromadzonych w korpusie „FoKo” - Ginter, Joanna (Neofilolog, 2026)
The article investigates orthographic errors produced by Ukrainian upper primary school students learning Polish in Pomerania. The study addresses a gap in research on the written production of Ukrainian learners, as orthography remains a marginal topic in Polish glottodidactics, despite its relevance for mastering all subsystems of the language. The analysis is based on 79 handwritten texts collected in the “FoKo” Learner Corpus of Polish, written by seventh- and eighth-grade students of Ukrainian origin between 2021 and 2023. The qualitative analysis applied involved identifying, classifying and interpreting errors with reference to cross-linguistic interference and features of Polish orthography. The results show that most errors stem from phonetic and graphic differences between Polish and Ukrainian/Russian, including confusion of letters representing the three sibilant series, difficulties with diacritics, and Cyrillic-based spelling habits. Learners also display errors typical of Polish pupils, particularly in the spelling of nasal vowels and the contrasts u–ó, rz–ż and ch–h. Error frequency does not strictly correlate with age or length of residence in Poland. The findings point to the need for more explicit and systematic orthographic instruction in Polish as a foreign language.